Ancient Egypt between Centralized and uncentralized Governing system - محسن الخفاجي, مزهر (Al-Adab Journal, 2018)
The experiences of the community and the individual through a continuous historical struggle . The process of forming a stste that lacks a centralized free will that is devoted to the desire of individuals to live safely in a community . Therefore the concept of freedom is meaningless unless individuals understand that it is in reality connected to Responsibility from others and for others. this philosophical progress . Will help us understand that kingdom-ship is a crucial factor of the state of Egypt, its land and people .the king of a city-state in Egypt is the leader of the government; he is restricted by the fatherhood of heaven acceptance to go to the public, it is a basic condition of the governing system and this holy fatherhood of heaven requires the blessing of the people . perhaps this concept made a totally centralized government controls all government levels , political , religious , economical and social, based on idea kings are qualified by heaven to rule and provide a base for this rule.The uncentralized political system was the main political system in Egypt before the age of dynasty ruling. However, this didn't last forAlong time because the dynasties of ancient Egypt have ruled by a totalitarian centralized government from the first dynasty to the fourth dynasty until the modern state . The exaggerated centralized government put administration and regional responsibility on one rule; the pharaoh and a number of his senior employees, who follow a centralized administration organized by a precise political , economical and administrational mechanism. Through this mechanism ancient Egyptian rulers kept a centralized governing system whatever its religious, political , economical , social means and types or ruling. This research focuses on the types of ruling systems in Egypt since the age of dynasties to the end of modern st.